Does fluoroscopy improve outcomes in paediatric forearm fracture reduction?. Issue 6 (June 2016) - Menachem, S.; Sharfman, Z.T.; Perets, I.; Arami, A.; Eyal, G.; Drexler, M.; Chechik, O.
Abstract : Aim: To compare the radiographic results of paediatric forearm fracture reduced with and without fluoroscopic enhancement to investigate whether fractures reduced under fluoroscopic guidance would have smaller residual deformities and lower rates of re-reduction and surgery. Materials and methods: A retrospective cohort analysis was conducted comparing paediatric patients with acute forearm fracture in two trauma centres. Demographics and radiographic data from paediatric forearm fractures treated in Trauma Centre A with the aid of a C-arm fluoroscopy were compared to those treated without fluoroscopy in Trauma Centre B. Re-reduction, late displacement, post-reduction deformity, and need for surgical intervention were compared between the two groups. Results: The cohort included 229 children (175 boys and 54 girls, mean age 9.41±3.2 years, range 1–16 years) with unilateral forearm fractures (83 manipulated with fluoroscopy and 146 without). Thirty-four (15%) children underwent re-reduction procedures in the emergency department. Fifty-three (23%) children had secondary displacement in the cast, of which 18 were operated on, 20 were re-manipulated, and the remaining 15 were kept in the cast with an acceptable deformity. Twenty-nine additional children underwent operation for reasons other than secondary displacement. There were no significant differences in re-reduction and surgery rates or in post-reduction deformities between the two groups. Conclusion: The use of fluoroscopy during reduction of forearm fractures in the paediatric population apparently does not have a significant effect on patient outcomes. Reductions performed without fluoroscopy were comparably accurate in correcting deformities in both coronal and sagittal planes. Highlights: Compared outcomes of pediatric forearm fracture reduction with and without fluoroscopy. The use of fluoroscopy during reduction of forearm fractures in the pediatric population apparently does not have a significant effect on patient outcomes. Reductions performed without fluoroscopy were comparable in correcting deformities in both coronal and sagittal planes.